2020
DOI: 10.1021/acs.jafc.0c03103
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Interesterified Medium- and Long-Chain Triacylglycerols Improves Lipid Metabolism and Reduces Inflammation in High-Fat Diet-Induced Obese Rats

Abstract: Medium- and long-chain triacylglycerols (MLCTs) were synthesized from rapeseed oil (RO), one kind of commonly used edible long-chain triacylglycerols (TGs), and then delivered to high-fat diet (HFD)-induced obese rats. Compared with RO, MLCT consumption exhibited more potent effects on reducing body and tissue weight gains, plasma TG, and total cholesterol (TC) levels and on improving hepatic TG, TC, fatty acid synthase, acetyl-CoA carboxylase, and lipoprteinlipase contents. Meanwhile, lower amounts of tumor n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 48 publications
2
17
0
Order By: Relevance
“…HFD can lead to liver enlargement and lipid accumulation while the increase in liver index and adiposity index indicates the presence of obesity to a certain extent (Cho et al., 2017 ). Obesity is commonly accompanied by disorders in lipid metabolism, and its most common presentation is abnormally elevated serum lipid levels (Du et al., 2020 ). Thus, serum TC, TG, LDL‐C, and HDL‐C levels are key indicators for evaluating lipid metabolism (Dechesne et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…HFD can lead to liver enlargement and lipid accumulation while the increase in liver index and adiposity index indicates the presence of obesity to a certain extent (Cho et al., 2017 ). Obesity is commonly accompanied by disorders in lipid metabolism, and its most common presentation is abnormally elevated serum lipid levels (Du et al., 2020 ). Thus, serum TC, TG, LDL‐C, and HDL‐C levels are key indicators for evaluating lipid metabolism (Dechesne et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…29,30 However, many studies on the physiological activity of MCTs did not include lauric acid glycerides, although lauric acid accounted for the majority of the limited resources of MCTs. 31 The data on the effects of LT on chronic diseases remain sparse. In the present study, we observed that high-dose LT reduced the BW of obese rats and lowered the TG levels in plasma and the liver.…”
Section: ■ Discussionmentioning
confidence: 99%
“…MCTs had no acute toxicity and did not promote the development of cancer . Furthermore, the MCTs have many health benefits because they have unique metabolic pathways, which is different from LCTs in the body. , However, many studies on the physiological activity of MCTs did not include lauric acid glycerides, although lauric acid accounted for the majority of the limited resources of MCTs . The data on the effects of LT on chronic diseases remain sparse.…”
Section: Discussionmentioning
confidence: 99%
“…The chloroform-methanol extraction method for fatty acid quantification was reported to be less than solvent-free triglyceride determination of membrane-bound fatty acids [ 17 ]. Furthermore, the use of MCT as the placebo control, although not directly affecting the crossover design, clearly was a questionable choice given the fact that MCT has demonstrated anti-inflammatory activity [ 18 , 19 ]. The original choice of the placebo was to maintain the same caloric value as the verum without a plan to use an active placebo.…”
Section: Discussionmentioning
confidence: 99%